2016
DOI: 10.1002/ejic.201600170
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Monomeric Aluminium Hydrazide towards Isocyanates and Isothiocyanates: Active Lewis Pair Behaviour versus Classical Insertion Reactions

Abstract: Abstract:Hydroalumination of H 10 C 5 N-N=C(Ad) with HAliBu 2 yielded the hydrazide H 10 C 5 N-N(AliBu 2 )Ad (4; Ad = adamantyl, NC 5 H 10 = piperidinyl). Compound 4 is monomeric and contains a highly strained AlN 2 heterocycle formed by a donor-acceptor interaction between the Al atom and the -N atom of the hydrazine. Two equivalents of the hydride afforded an adduct with an HAliBu 2 molecule coordinated to 4 by an Al-N and a 3c-2e Al-H-Al bond (5). tBuN=C=O did not insert into the relatively weak Al←N donor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…The formation of compound 6 clearly demonstrates the reactivity of 5 as a masked FLP and its ability to act as an ambiphilic ligand. Similar compounds have been obtained with an Al i Bu 2 analogue of 5 and several Al/P based FLPs . NMR experiments showed that 5 and 6 could be quantitatively interconverted by combining stoichiometric quantities of 5 and Me 2 GaH or 6 and H 10 C 5 N–N=C(C 9 H 14 ).…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…The formation of compound 6 clearly demonstrates the reactivity of 5 as a masked FLP and its ability to act as an ambiphilic ligand. Similar compounds have been obtained with an Al i Bu 2 analogue of 5 and several Al/P based FLPs . NMR experiments showed that 5 and 6 could be quantitatively interconverted by combining stoichiometric quantities of 5 and Me 2 GaH or 6 and H 10 C 5 N–N=C(C 9 H 14 ).…”
Section: Resultssupporting
confidence: 64%
“…The sterically less demanding i Bu 2 AlH gave both types of products upon treatment of the metal hydride with the hydrazone in the appropriate stoichiometric ratio of 1:1 or 2:1. Interestingly the reaction of the aluminium hydrazide with excess metal hydride to give the hydride adduct failed, while treatment of the hydride adduct with stoichiometric amounts of hydrazone at elevated temperatures afforded the hydrazide in reasonable yield …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations